Successful and unsuccessful recruitment and retainment strategies in a UK multicentre drug trial for a rare chronic pain condition which performed above target. Issue 3 (August 2020) - Bisla, Jatinder; Ambler, Gareth; Frank, Bernhard; Gulati, Sumit; Hocken, Poppy; James, Mairi; Kelly, Joanna; Keshet-Price, Jocelyn; McCabe, Candy; McGylnn, Deborah; Padfield, Nick; Pang, David; et al.
Introduction: Recruitment into trials in rare chronic pain conditions can be challenging, so such trials consequently are underpowered or fail. Methods: Drawing from our experience in conducting, to date, the largest academic trial in a rare chronic pain condition, complex regional pain syndrome, we have identified recruitment and retention strategies for successful trial conduct. Results: We present 13 strategies grouped across the categories of 'setting the recruitment rate', 'networking', 'patient information', 'trial management' and 'patient retention'. Moreover, six recruitment risks are also discussed. A conservative recruitment estimate, based on audits of newly referred patients to the trial centres without taking into account availability of 'old' patients or recruitment from outside centres, and assuming a 55% patient refusal rate yielded accurate numbers. Conclusion: Appreciation of these identified recruitment challenges and opportunities may contribute to supporting prospective investigators when they design clinical trials for chronic pain patient population groups where it has been historically difficult to conduct high-quality and robust clinical trials.